2011
DOI: 10.1007/s00467-011-1788-y
|View full text |Cite
|
Sign up to set email alerts
|

Kidney and urinary tract development: an apoptotic balancing act

Abstract: Development of the mammalian urogenital system requires a balance between survival and programmed cell death. Pro-survival molecules are crucial in preserving metanephric mesenchyme viability, and thus allowing nephrogenesis to proceed. At the same time, localized areas of apoptosis mediated by effector caspases are required for the appropriate morphogenesis of the kidney and urinary tract. Activation of the intrinsic pathway of apoptosis seems to be fundamental to the progression of cell death necessary to ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 55 publications
(86 reference statements)
0
9
1
1
Order By: Relevance
“…The reason for these results is not immediately clear. It is noteworthy that apoptosis plays an active role in nephrogenesis [26] and increased renal apoptosis can still be detected in the 8-week-old offspring in a maternal protein restriction model [27]. Since we observed that p53 pathway is a significantly regulated KEGG pathway in 1-day-old kidney (data not shown), effects of apoptosis on numbers of nephron in adulthood require further investigation.…”
Section: Discussionmentioning
confidence: 67%
“…The reason for these results is not immediately clear. It is noteworthy that apoptosis plays an active role in nephrogenesis [26] and increased renal apoptosis can still be detected in the 8-week-old offspring in a maternal protein restriction model [27]. Since we observed that p53 pathway is a significantly regulated KEGG pathway in 1-day-old kidney (data not shown), effects of apoptosis on numbers of nephron in adulthood require further investigation.…”
Section: Discussionmentioning
confidence: 67%
“…Imbalance between proliferation and apoptosis has been widely known to play an important role in a variety of physiological processes, such as embryonic growth, development, proliferation of cells, or in a variety of pathological processes such as autoimmune diseases, tumours, and organ damage . A variety of adverse factors, such as hypoxia and malnutrition, can break the balance between apoptosis and proliferation and cause pathological changes in the kidneys, such as reducing the number of glomeruli . In this study, no significant difference in the proliferation index was observed between IUGR pups and control pups whose mothers were fed a normal diet.…”
Section: Discussionmentioning
confidence: 48%
“…A dynamic balance between cell proliferation and death has been revealed to be directly associated with the regulation of the renal glomerular number . Apoptosis has been associated with the reduction in renal glomerular number in a rat IUGR model induced by bilateral uterine artery ligation .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations